2018
DOI: 10.1038/s41598-018-30396-8
|View full text |Cite
|
Sign up to set email alerts
|

Microcavity-integrated graphene waveguide: a reconfigurable electro-optical attenuator and switch

Abstract: Graphene has been widely utilized in optoelectronic applications due to its high carrier mobility, and extremely fast optical response. Microcavity-integrated graphene waveguide structure is one basic module of integrated photonic devices which can greatly improve the light-matter interaction strength. The enhanced optical absorption in the undoped graphene layer results from the light trapping and the corresponding long light-graphene interaction length. Tuning the Fermi energy level of the graphene layer ena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…The wavelength-dependent absorption A(λ) was inferred from the wavelength-dependent transmittance T(λ) and reflectance R(λ) (A(λ) = 1 − R(λ) − T(λ)) [ 71 , 72 ], by using the Wave Optics Module of Comsol Multiphysics software. Graphene optical properties were simulated by a wavelength-dependent complex refractive index [ 73 , 74 ], where the single-layer graphene permittivity was [ 75 , 76 , 77 ]: being (2.5) [ 78 , 79 ], t G (0.35 nm) [ 80 , 81 ], and σ ( ω ) the intrinsic contribution to the graphene relative permittivity, the thickness of single layer graphene and the graphene optical conductivity, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The wavelength-dependent absorption A(λ) was inferred from the wavelength-dependent transmittance T(λ) and reflectance R(λ) (A(λ) = 1 − R(λ) − T(λ)) [ 71 , 72 ], by using the Wave Optics Module of Comsol Multiphysics software. Graphene optical properties were simulated by a wavelength-dependent complex refractive index [ 73 , 74 ], where the single-layer graphene permittivity was [ 75 , 76 , 77 ]: being (2.5) [ 78 , 79 ], t G (0.35 nm) [ 80 , 81 ], and σ ( ω ) the intrinsic contribution to the graphene relative permittivity, the thickness of single layer graphene and the graphene optical conductivity, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, under thermal-equilibrium conditions, it is found that the refractive index of PNIPA exhibits a classical Boltzmann distribution depending on the heating power and manifests the threshold of the phase transition. This strategy combines microcavity photonics with microfluidics and phase change materials, in which not only the basic properties of phase change materials are well characterized with dual-mode, self-referencing spectra, but also the functional photonic devices, such as optical switches 26 and optical memories 27 , can be constructed.…”
Section: Introductionmentioning
confidence: 99%
“…Another approach to enhance the absorption of graphene is to exploit the constructive interference of the electromagnetic radiation inside an optical multilayer structure. The multilayer Fabry–Perot (FP) filter is one of the most effective structures allowing for a high absorption enhancement. …”
Section: Introductionmentioning
confidence: 99%